İslâm hukukunda tarafların ön anlaşma ile belirledikleri muhayyerlikler : şart muhayyerliği - Avcı, Fatih (My University, 2023)
Tarih boyunca insanlar sahip olmadıkları ve ihtiyaç duydukları şeyleri elde edebilmek için alışveriş yapmışlardır. Alışverişin yöntemleri değişmekle birlikte temel amacı hiç değişmemiştir. Gün geçtikçe edinilen tecrübeler, tarafların tam olarak memnun olacağı ideal sözleşme yapısının elde edilebilmesi için alışveriş yöntemlerini şekillendirmiştir. Şart kurumu, bu gelişimin en önemli adımlarından biridir. Taraflar şart sayesinde tam olarak memnun olabileceklerini düşündükleri sözleşmeyi kendi iradelerine göre tasarlamaktadırlar. Sözleşmenin kuruluşunu taraflardan birinin tek taraflı iradesine bağlayan mutlak iradî şart da eski zamanlardan beri ihtiyaç duyulan işlemlerdendir. Öyle ki bu şarta, genel esaslara aykırı olmasına rağmen istisna olarak Roma hukukunda “pactum displicentiae”, İslâm hukukunda “şart muhayyerliği” vb. isimler adı altında izin verilmiştir. Türk hukukunda “beğenme koşuluyla satış” olarak isimlendirilen bu şart, günümüzde istisnaî bir işlem olmaktan çıkıp Kara Avrupası kanunlarındaki yerini almıştır. Fakat hukukçular onun hukuki niteliği hususunda hala görüş birliğine varamamışlardır. Nitekim, Kara Avrupası hukukunda beğenme koşuluyla satışı bir “şart” olarak görenlerin yanı sıra “ön sözleşme”, “opsiyon”, “isimsiz-aynî sözleşme” veya kabul bekleyen bir “icap” görüşleriyle açıklayan hukukçular da vardır. Onun şart olduğunu kabul edenler ise alelade şart mı yoksa mutlak iradî bir şart mı olduğu hususunda tartışmışlardır. Şart muhayyerliği fıkıh kitaplarının satış sözleşmesi bölümlerinde en başta ele alınacak kadar önemli olmasına rağmen tespit edebildiğimiz kadarıyla İslâm hukukunda onun hukuki niteliği üzerine yapılmış bir inceleme yoktur. Hatta bazı yazarlar tarafından beğenme koşuluyla satışın İslâm hukukundaki karşılığının sevm-i şirâ (satış pazarlığı) olduğu veya bu koşulun takyidî bir şart olduğu söylenerek onun hukuki niteliği hakkında katılmadığımız bir tespit yapılmaktadır. Bu çalışmanın başlıca amacı, şart muhayyerliğinin İslâm hukukunda sözleşmelerdeki öneminin sebebini tespit etmek, onun hukuki niteliğini belirlemek ve fıkıh kitaplarında dağınık olarak yer alan hükümlerini bütüncül bir şekilde ele almaktır.

Throughout the history, people have shopped to get what they don't have and what they need. Although the methods of shopping have changed, the main purpose has never changed. The experiences gained day by day have shaped the shopping methods in order to obtain the ideal contract structure that the parties will be fully satisfied with. The “condition” institution is one of the most important steps in this development. The parties design the contract according to their own will, which they think will be fully satisfied with the condition. “Purely potestative condition”, which binds the establishment of the contract to the unilateral will of one of the parties, is one of the transactions that have been needed since ancient times. So much so that this conditional pactum displicentiae in Roman law, “khiyār al-shart” in Islamic law, etc. Although it is against the general principles of these laws, it is allowed as an exception under the name of names. This condition, which is called sale on approval in Turkish law, has ceased to be an exceptional transaction today and has taken its place in the laws of Continental European law. However, jurists still have not reached a consensus on its legal nature. As a matter of fact, in Continental European law, besides those who see sales on approval as a “condition”, there are also lawyers who explain it with the views of “preliminary contract”, “option”, “in kind contract” or an “offer” awaiting acceptance. Those who accept that it is a condition have debated whether it is an ordinary condition or an purely potestative condition. Although khiyar al-shart is important enough to be discussed at the beginning in the sales contract chapters of fiqh books, as far as we can determine, there is no examination of its legal nature in Islamic law. In fact, it is said that the equivalent of selling under the sale on approval in Islamic law is savm shirā (sales bargain) so made a determination about its legal natüre and its similarity with its khiyār al-shart is overlooked. Again, in some modern texts, it is said to be a takyīdī shart (restrictive condition) and in our opinion, an incorrect determination is made about its legal nature. The main purpose of this study is to determine the reason for the importance of khiyār al-shart in Islamic law contracts, to determine its legal nature and to deal with its provisions that are scattered in fiqh books in an organized manner.
Keywords: Beğenme Koşuluyla Satış; Condition; Fesih; Islamic Law; İslam hukuku; İslâm Hukuku; İslamic law; Khiyar al-Shart; Muhayyerlik; Mutlak İradî Şart; On Approval; Purely Potestative Condition; Sale on Approval; Selling on the Condition of Experience and Inspection; Şart; Şart Muhayyerliği; Tecrübe ve Muayene Şartıyla Satım; Termination